EVALUASI PELAKSANAAN PROGRAM REMEDIAL DENGAN MENGGUNAKAN MODEL FORMATIF-SUMATIF PADA PELAJARAN MATEMATIKA KELAS V - Sianipar, Mariska; Rusdi, Muhammad; Suratno, Suratno (Program Magister Teknologi Pendidikan Universitas Jambi, 2013)
The remedial is a learning system which is taken based on a comprehensive diagnosis referred to find what is necessary to the students. One of the remedial activity is called an improvement given to the students. SDN 47 Kota Jambi is one of the school that remedial program is applied. This research examines the implementation of remedial program on mathematic subject, obstacles to the implementation of remedial program, intentions, and the effectiveness of teaching remedial on mathematics. This research applies descriptive approach. Interview, observation, and documentation were used to collect data. Interactive analysis model are connected with four interrelated components such as data collection, data reduction, data presentment and conclusion. These four criteria were used as validity data checking: level of credence, diversions, dependence, and the level of certainty. The results of this research have shown that (1) The implementation of remedial formative and summative program in SD 47 Kota Jambi has been accomplished as well. The school is also support the implementation of this program. As for the parents, the remedial program means giving a chance to the students to improve their mark. (2) This research found that student’s character, family, and society are the problems in the implementation of remedial program. As for the teachers, it is quite difficult to set the implementation time whereas as for the students, they are facing difficulties when dealing with narrative text, have lack of attention to the subject explained by the teacher and some of them are less-prepared when facing the remedial. (3) This remedial program has produced students who are diligent and built confident within themselves, getting more and more accurate when they have to dealing with their task and problems. (4) Still there are some improvements that needs to be achieved such as they are not develop their attitude and habits that encourage the sense of self-studious and confidence. Thus, sometimes they did not do their homework given by their teacher. (5) Remedial teaching on mathematics is very effective and brings good effect to the students both in school and home. Keyword : program evaluation, remedial, formative-summative model